Kemampuan Siswa Dalam Menyelesaikan Soal Matematika High Order Thinking Skills Berdasarkan Langkah Polya Pada Materi Pola Bilangan - Atiyah Nasyiwa; Nurul Hikmah; Wahidaturrahmi; Sripatmi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe the level of students' ability in solving High Order Thinking Skills (HOTS) math problems based on the Polya step in the number pattern material for class VIII SMPN 2 Praya in the 2021/2022 academic year. The type of research used is descriptive qualitative research. The research subjects were 30 students who were selected with a sampling technique using purposive sampling. The data collection techniques using tests and interviews. The data analysis technique was carried out using the data reduction stage, the data presentation stage, and the conclusion drawing stage. The results of the students study with a highly capable of meeting each step of rhe Polya, students with the ability has not been able to meet the fourth stage of reexamining the results obtained, and the students with enough ability is not able to meet the phase of implementing the plan and reexamining the results obtained. Whereas, students with the less abilitiy were not able to make a plan, implement a plan and reexamine the results obtained and greatly less ability were unable to fulfill all of the Polya steps. Overall, the average students ability to solve the mathematics problem of HOTS by Polya measures fall below the category. The majority of students do not write down what is known and asked for, struggle to make plans and carry out plans, miscalculate calculation, and do not know how to reexamine the results.